Structural Evaluation and Root Cause Analysis of Vehicular Box Culvert (VBC) Defects in Section 6A of ECRL Project - HAZIQ AFIQ SOLEH, MUHAMMAD HAZIQ AFIQ BIN MOHD SOLEH; MUSLI NIZAM, MUSLI NIZAM BIN YAHYA; Annuar Abdullah (Progress in Engineering Application and Technology, 2024)
This research investigates the concrete defects in Vehicular Box Culverts (VBCs) within Section 6A of the East Coast Rail Link (ECRL) project. Notably, a significant concrete defect was identified at Culvert 192 (CH384+580), featuring cracks in the top slab and wing wall. The study aims to analyze concrete defects on the VBCs within work zone 2 area in section 6A and identify their contributing factors. The methodology includes detailed site visits, where 21 VBCs were inspected, and concrete defects such as shrinkage cracks, water seepage, and discoloration were documented. Quantitative analysis using bar and pie charts revealed that discoloration was the most frequent defect, while medium severity levels predominated. Factors contributing to defects include poor soil compaction, inadequate waterproofing, and construction practices. An AutoCAD 3D model was utilized to illustrate the loading conditions and their impact on VBC settlement, highlighting the influence of vehicular loads and soil pressure. Findings indicate that the majority of defects are manageable through standard maintenance, although some structural issues, such as settlement cracks, pose significant risks. This research underscores the need for improved construction practices and maintenance strategies to enhance VBC durability and integrity in large-scale infrastructure projects like the ECRL.